Sharia Based Marketing Strategies in the Development of Halal Food and Beverage MSMEs in North Purwokerto - Marya, Anita (Journal of Principles Management and Business, 2025)
This study aims to analyze the implementation of Sharia-based marketing strategies in halal food and beverage MSMEs in Purwanegara Village, North Purwokerto District, Indonesia. The study employed a qualitative descriptive method, with data collection techniques including in-depth interviews, observation, and documentation of 23 MSMEs (11 food MSMEs and 12 beverage MSMEs). The results indicate that MSMEs have integrated Sharia values ​​into their marketing practices, encompassing aspects of product, price, place, promotion, and service ethics. Food MSMEs place greater emphasis on product halalness and affordability, while beverage MSMEs emphasize flavor innovation and digital branding. The implementation of Sharia values, such as honesty, price transparency, friendly service, and ethical promotion, has been shown to increase consumer trust and strengthen customer loyalty. These findings align with previous research but provide a new contribution by identifying differences in marketing strategies between food and beverage MSMEs. This study also confirms that the implementation of Sharia marketing strategies not only strengthens competitiveness but also creates business sustainability based on the values ​​of blessing.